Model Controlling Economic Stability Through Interest Rate at TIMI Countries (Thailand, Indonesia, Malaysia, India) - Br Tarigan, Nuragus Listiyani; Rangkuty, Dewi Mahrani; Abdiyanto Abdiyanto (International Journal of Economics, Commerce, and Management, 2024)
This study examines the influence of monetary policy, particularly interest rates, on economic stability in the TIMI countries (Thailand, India, Malaysia, and Indonesia). It underscores the vital role of interest rates in controlling inflation and stimulating economic growth. Utilizing a Vector Autoregression (VAR) model, the research analyzes the reciprocal relationships between crucial economic indicators such as GDP, CPI, exchange rates, consumption, interest rates, and trade balances from 2008 to 2022. For instance, adjustments in interest rates can influence investment levels, consumption patterns, and inflation rates, thereby affecting overall economic activity. The Granger causality tests indicate that short-term relationships between these variables are insignificant, but long-term interactions are evident. This supports the Johansen cointegration results, which confirm two cointegrated equations at the 5% significance level. The study emphasizes maintaining interest rate stability for sustainable economic growth and price stability. It highlights that fluctuations in interest rates, influenced by global economic conditions and domestic economic policies, play a crucial role in the economic performance of TIMI countries. Recommendations for central banCM include implementing responsive and adaptive interest rate policies to manage inflation, foster economic growth, and maintain exchange rate stability. This approach is essential for addressing disparities in income, education, healthcare, and technology access, which are critical for equitable economic development. In conclusion, this research underscores the importance of a nuanced understanding of monetary policy's impact on economic stability and the need for coordinated efforts between fiscal and monetary authorities to achieve long-term